The Profile of Blindness Aetiology in Children of SLB/A Denpasar - Anak Agung Ayu Sukartini Djelantik (Journal of Global Pharma Technology, 2016)
Introduction: Blindness in children is one global problem that adressed by the World Health Organization (WHO) to achieve VISION 2020